2019
DOI: 10.1111/sjoe.12275
|View full text |Cite
|
Sign up to set email alerts
|

Should Mobile Marketers Collect Data Other Than Geo‐Location?*

Abstract: We take today's mobile marketing data landscape as a starting point and consider a duopoly model of third-degree price discrimination in which firms can complement geo-location information with data on consumer flexibility of varying quality. We show that, depending on consumer heterogeneity, higher-quality flexibility

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Although this admittedly corresponds to some assumed level of consumer myopia, we consider this both practical and realistic in e-commerce. 5 The sequence of decisions is as follows. Retailers simultaneously and independently decide on the privacy-intrusiveness of their websites, q i .…”
Section: A Theoretical Model Of Privacy In E-commercementioning
confidence: 99%
“…Although this admittedly corresponds to some assumed level of consumer myopia, we consider this both practical and realistic in e-commerce. 5 The sequence of decisions is as follows. Retailers simultaneously and independently decide on the privacy-intrusiveness of their websites, q i .…”
Section: A Theoretical Model Of Privacy In E-commercementioning
confidence: 99%
“…Fudenberg and Villas-Boas (2006) andEsteves (2009a) provide a review of this literature.7 If-for a given uniform price of the rival-both firms optimally charge a higher price to the same consumer group, then according to Corts this market is characterized by best-response symmetry In all other cases best-response asymmetry applies.8 In a static setting,Thisse and Vives (1988) were the first to demonstrate the negative effect of price discrimination on prices and profits, which leads to a prisoners' dilemma (see, for a similar result,Bester & Petrakis, 1996;Liu & Serfes, 2004;Shaffer & Zhang, 1995). More recent literature showed that firms may be better off with price discrimination under best-response asymmetry: The positive profit effect is demonstrated in articles that start with an asymmetric (more advantageous to one of the firms) situation [see Zhang (2000, 2002),Carroni (2016)] and in articles that assume imperfect customer data (as inChen et al 2001;Liu & Shuai, 2016;Baye & Sapi, 2019).…”
mentioning
confidence: 92%